LIMBAH SAYURAN REBUNG BAMBU SEBAGAI MIKROORGANISME LOKAL (MOL) DALAM PEMBUATAN PUPUK ORGANIK: Perspektif Pengelolaan Sampah Organik - Waode Rustiah Rustiah; Dewi Arisanti; Mujahidah Basarang; Nur Qadri Rasyid; Andi Fatmawati (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2022)
This Community Service Program aims to enhance motivation, knowledge and skills about techniques of producing organic fertilizer from household waste by utilizing local microorganisms (MOL), which can replace agricultural chemicals. Training of using of bamboo shoots vegetable waste, as MOL in the manufacture of organic fertilizer, provides enlightenment in the manufacture of liquid organic fertilizer, and encourages local community businesses independently. MOL contain micro and macro nutrients and bacteria that have the potential to decompose organic matter, stimulate plant growth and act as an activator or decomposer in composting. Organic fertilizers are fertilizers composed of living matter that is processed through a process of decomposition (decomposition) by decomposing bacteria. The method of this community service consists of three phase, namely: 1) the preparation phase, including counseling to the community of Bonto Kio Village, Kec. Minasate'ne, Kab. Pangkep on the using of MOL as liquid organic fertilizer from bamboo shoots vegetable waste; 2) the implementation phase, including direct practice of the material presented; and 3) question and answer or discussion on the use of MOL as organic fertilizer. The results show that this counseling and training success to enhance motivation the community and shows that their level of curiosity and interest in making liquid organic fertilizer using local microorganisms is quite high, such as to increase soil microbes which in turn maintain the fertility of their agricultural land. The community's understanding of the benefits of this activity is very large, as can be seen from the desire to independently make MOL-based organic fertilizers.